The Impact of Artificial Intelligence on Generation Z Customer Experience in Agricultural E-Commerce: A Case Study of Shopee in Vietnam - Hoang, Hien Thi Thu; Do, Ha Thi Thu; Phan, Anh (Research on World Agricultural Economy, 2026)
The study aims to explore the impact of artificial intelligence on the online shopping experience of Generation Z consumers, focusing on the agricultural products offered on online shopping platforms such as Shopee in Vietnam. The study assesses the main features of artificial intelligence, including AI-based chatbots, AI-based price generation, AI-based recommendation systems, and AI-based image search, and their contributions to the shopping experience, personalization, and satisfaction, especially for products such as organic fruits, vegetables, and rice, which accounted for 20 percent of the sales of Shopee in Vietnam in 2024. The study is based on a quantitative analysis of behavioral patterns and perceptions and reveals the impact of artificial intelligence on the shopping experience of Generation Z consumers, thereby contributing to the development of the global agricultural economy and food security in developing countries. The study also reveals the impact of artificial intelligence on the shopping behavior and loyalty of young Vietnamese consumers in the digital agricultural economy, which is in line with the recent initiatives of the Food and Agriculture Organization on artificial intelligence-based agrifood systems. ER